2021
DOI: 10.1007/s12035-021-02507-6
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis

Abstract: The dopaminergic system plays an essential role in maintaining homeostasis between the central nervous system (CNS) and the immune system. Previous studies have associated imbalances in the dopaminergic system with the pathogenesis of multiple sclerosis (MS). Herein, we investigate the protein levels of dopaminergic receptors (D1R and D2R) in different phases of the experimental autoimmune encephalomyelitis (EAE) model. We also examined if the treatment with pramipexole (PPX) -a dopamine D2/D3 receptor-preferr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…In particular, pramipexole (PPX) (1 mg/kg), a D2/D3 receptor-preferring agonist, has been shown to reduce depressive-like behavior in EAE animal models. 90 Therefore, D2R might be implicated in the neuroinflammatory responses in EAE-related mood disorders. Another study has demonstrated that isosibiricin, a natural coumarin compound, could inhibit microglial activation by targeting D1/D2 receptor-dependent nucleotide binding domain like receptor protein 3 (NLRP3)/caspase-1 inflammasome pathway.…”
Section: Monoamine Neurotransmitters/alkaloid Neurotransmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, pramipexole (PPX) (1 mg/kg), a D2/D3 receptor-preferring agonist, has been shown to reduce depressive-like behavior in EAE animal models. 90 Therefore, D2R might be implicated in the neuroinflammatory responses in EAE-related mood disorders. Another study has demonstrated that isosibiricin, a natural coumarin compound, could inhibit microglial activation by targeting D1/D2 receptor-dependent nucleotide binding domain like receptor protein 3 (NLRP3)/caspase-1 inflammasome pathway.…”
Section: Monoamine Neurotransmitters/alkaloid Neurotransmittersmentioning
confidence: 99%
“…Given this evidence, dopaminergic receptors have been used as potential pharmaceutical targets in MS-related mood disorders. In particular, pramipexole (PPX) (1 mg/kg), a D2/D3 receptor-preferring agonist, has been shown to reduce depressive-like behavior in EAE animal models . Therefore, D2R might be implicated in the neuroinflammatory responses in EAE-related mood disorders.…”
Section: Monoamine Neurotransmitters/alkaloid Neurotransmittersmentioning
confidence: 99%